Trouble in Goshen : plain folk, Roosevelt, Jesus, and Marx in the Great Depression South - Smith, Fred C., 1949 August 8- (University Press of Mississippi, 2014)
The Great Depression emboldened Americans to tolerate radical experimentation in search of solutions to economic problems. Amongst the thorniest of those problems was that of Southern poverty; indeed, FDR claimed in 1933 that Southern rural poverty was the nation's 'number one economic problem'. In 'Trouble in Goshen' Fred C. Smith focuses on three communities designed and implemented to solve that problem. This book examines the economic and social theories - and their histories - that resulted in the creation and operation of the most aggressive and radical experimentation in the United States.